Green Processing of Nanofibers for Regenerative Medicine. Issue 10 (17th December 2012) - Krishnan, Ranganathan; Sundarrajan, Subramanian; Ramakrishna, Seeram
Abstract Electrospinning of polymer scaffolds is mostly carried out using organic solvents, but the drawbacks are: solvent costs, environmental hazards, and presence of traces of solvent impurities. The use of water‐soluble polymers (WSPs), water or aqueous solutions as an electrospinning medium (green processing) is a very attractive method to avoid such issues. However, a few WSP such as polyelectrolytes are not spinnable as such, but have been electrospun by addition of WSPs, additives, and salts. This paper covers solution properties, polyelectrolyte nanofibrous scaffolds (polysaccharides, biopolymers, etc.), fabrication through green processing, and their regenerative medical applications such as wound dressing, drug delivery, and tissue engineering. This is the first review to cover the above issues, the drawbacks of current methods, and future challenges.<inline-graphic xlink:href="ark:/27927/pgg3j5r6krv" content-type="mame201200323-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />